Cellular Electrophysiology of Iron-Overloaded Cardiomyocytes - Siri-Angkul, Natthaphat; Xie, Lai-Hua; Chattipakorn, Siriporn C.; Chattipakorn, Nipon (Frontiers in Physiology, 2018)
Iron, the most abundant transition metal element in the human body, plays an essential role in many physiological processes. However, without a physiologically active excretory pathway, iron is subject to strict homeostatic processes acting upon its absorption, storage, mobilization, and utilization. These intricate controls are perturbed in primary and secondary hemochromatoses, leading to a deposition of excess iron in multiple vital organs including the heart. Iron overload cardiomyopathy is the leading cause of mortality in patients with iron overload conditions. Apart from mechanical deterioration of the siderotic myocardium, arrhythmias reportedly contribute to a substantial portion of cardiac death associated with iron overload. Despite this significant impact, the cellular mechanisms of electrical disturbances in an iron-overloaded heart are still incompletely characterized. This review article focuses on cellular electrophysiological studies that directly investigate the effects of iron overload on the function of cardiac ion channels, including trans-sarcolemmal and sarcoplasmic reticulum Ca2+ fluxes, as well as cardiac action potential morphology. Our ultimate aim is to provide a comprehensive summary of the currently available information that will encourage and facilitate further mechanistic elucidation of iron-induced pathoelectrophysiological changes in the heart.